Gene expression regulation and secretory activity of mesenchymal stem cells upon in vitro contact with microarc calcium phosphate coating; International Journal of Molecular Sciences; Vol. 21, iss. 20 - Litvinova L. S. Larisa Sergeevna; Yurova K. A. Kristina Alekseevna; Shupletsova V. V. Valeria Vladimirovna; Khaziakhmatova O. G. Olga Gennadjevna; Malashchenko V. V. Vladimir Vladimirovich; Shunkin E. O. Egor Olegovich; Melashchenko E. S. Elena Sergeevna; Todosenko N. M. Nataljya Mikhaylovna; Khlusova M. Yu. Marina Yurjevna; Sharkeev Yu. P. Yury Petrovich; Komarova E. G. Ekaterina Gennadjevna; Sedelnikova M. B. Mariya Borisovna; et al. (2020, 2020)
The manufacture of biomaterial surfaces with desired physical and chemical properties that can directly induce osteogenic differentiation without the need for biochemical additives is an excellent strategy for controlling the behavior of mesenchymal stem cells (MSCs) in vivo. We studied the cellular and molecular reactions of MSCs to samples with a double-sided calcium phosphate (CaP) coating and an average roughness index (Ra) of 2.4-4.6 µm. The study aimed to evaluate the effect of a three-dimensional matrix on the relative mRNA expression levels of genes associated with the differentiation and maturation of MSCs toward osteogenesis (RUNX2, BMP2, BMP6, BGLAP, and ALPL) under conditions of distant interaction in vitro. Correlations were revealed between the mRNA expression of some osteogenic and cytokine/chemokine genes and the secretion of cytokines and chemokines that may potentiate the differentiation of cells into osteoblasts, which indicates the formation of humoral components of the extracellular matrix and the creation of conditions supporting the establishment of hematopoietic niches.